National Identities in Contemporary Media. Introduction to the Special Issue - Constantopoulou, Christiana (Social Cohesion and Development, 2024)
Collective identities (as it is the national identity) are an object of continuous process, negotiation and redefinition (in the field of private as well as in the field of public discourses –such as the media discourse). Two hundred years after the creation of the so called “romantic nations” (among which modern Greece) how the contemporary media define the world? Are “national” identities still important or solidarities among people follow different (such as religious, technological or simply “monetary”) inspirations of “belonging”? How the contemporary “identities” are shaped and how are they “reported” by the contemporary media and political discourse? The articles of this volume, based on research data and analyses contribute to answer the question: what is the national idea nowadays?